2013
DOI: 10.1002/mbo3.117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating bacterial community structures in oil collected from the sea surface and sediment in the northern Gulf of Mexico after the deepwater horizon oil spill

Abstract: On page 496, under the heading "Bacterial community in sediment and sediment overlying water", the terms SC and SG have been wrongly swapped in some places.The paragraph should read like the following:The pyrosequencing identified diverse bacterial groups in sediments from stations SG and SC, with 111 and 95 genera from 16 and 14 phyla, respectively (Table 1). In comparison, bacteria in the overlying water of SC sediment (SC-OW) were much less diverse, with 35 genera from 3125 OTUs. The bacterial communities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 0 publications
4
33
2
Order By: Relevance
“…Overall, the dominance of Proteobacteria observed in this study is consistent with previous studies from DWH impacted environments including deep-sea sediments (Kimes et al, 2013, Liu and Liu 2013, Mason et al, 2014, the water-column (Hazen et al, 2010, Baelum et al, 2012, Mason et al, 2012, Redmond & Valentine 2012, Rivers et al, 2013, Yang et al, 2014 and coastal beach ecosystems (Koskta et al, 2011, Newton et al, 2013. These data are also consistent with the diverse number of already known oil degrading bacteria (for reviews see; Atlas, 1981, Head et al, 2007, Yakimov et al, 2007 (Rinke et al, 2013) that is based upon genomes sequences of several small cells including Candidatus Parvarchaeum, Candidatus Micrarchaeum, Candidatus Nanosalina, andCandidatus Nanosalinarum (Narasingaro et al, 2012, Baker et al, 2010).…”
Section: Bacterial and Archaeal Community Structuresupporting
confidence: 93%
See 2 more Smart Citations
“…Overall, the dominance of Proteobacteria observed in this study is consistent with previous studies from DWH impacted environments including deep-sea sediments (Kimes et al, 2013, Liu and Liu 2013, Mason et al, 2014, the water-column (Hazen et al, 2010, Baelum et al, 2012, Mason et al, 2012, Redmond & Valentine 2012, Rivers et al, 2013, Yang et al, 2014 and coastal beach ecosystems (Koskta et al, 2011, Newton et al, 2013. These data are also consistent with the diverse number of already known oil degrading bacteria (for reviews see; Atlas, 1981, Head et al, 2007, Yakimov et al, 2007 (Rinke et al, 2013) that is based upon genomes sequences of several small cells including Candidatus Parvarchaeum, Candidatus Micrarchaeum, Candidatus Nanosalina, andCandidatus Nanosalinarum (Narasingaro et al, 2012, Baker et al, 2010).…”
Section: Bacterial and Archaeal Community Structuresupporting
confidence: 93%
“…These sediment communities resembled those previously observed in GoM sediments (e.g. Lanoil et al, 2001) suggesting that sediment microbial communities had returned to pre-spill community structures (Liu & Liu 2013).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The authors showed that members of Oceanospirillales can respond rapidly to aliphatic hydrocarbons as part of oil spill in marine environment. In another study, Liu and Liu (2013) investigated bacterial community structure in oil samples using next-generation sequencing of 16S rRNA including oil mousses collected on sea surface and salt marshes during the Deepwater Horizon oil spill and oil deposited in sediments adjacent to the wellhead 1 year after the spill. Based on molecular phylogeny of generated data, the authors found that Erythrobacter, Rhodovulum, Stappia, and Thalassospira belonging to Alphaproteobacteria were most prevalent in oil mousses, and the authors accounted their occurrence with high temperature and strong irradiance observed in surface water of the Gulf of Mexico.…”
Section: Biodegradation Of Polychlorinated Biphenyls In Marine Enviromentioning
confidence: 99%
“…Annweiller reported intermediates such as 2,3-dihydroxy naphthalene; 2-carboxynnarmic acid and phthalic and benzoic acid were identified in addition to typical metabolites of naphthalene degradation known from mesophiles in the pathway of B. thermoleovorans. Thalassospira is also implicated in degradation of fluorene and naphthalene and was found to be associated with oil on water surface during the DWH blowout previously by Liu and Liu [20,21].…”
Section: Introductionmentioning
confidence: 91%